Legal Protection of Borrower's Personal Data in Online Loan Application Services - Radea Respati Paramudhita (Sean Institute, 2025)
The rapid development of information technology has driven the emergence of various digital financial services, one of which is online lending applications. However, behind this ease of access, various problems have arisen related to the misuse of borrowers' personal data by service providers and third parties. This study aims to analyze the legal protection of borrowers' personal data in online lending applications and to assess the effectiveness of applicable regulations in Indonesia. The research method used is a normative juridical approach with a statutory and conceptual approach. Data was obtained through a literature review of laws and regulations such as Law Number 27 of 2022 concerning Personal Data Protection, the Electronic Information and Transactions (ITE) Law, the Financial Services Authority Regulation, and regulations related to financial technology. The results show that legal protection of borrowers' personal data in online lending services in Indonesia has not been optimally implemented, despite the legal basis provided by the ITE Law, POJK No. 77/POJK.01/2016, and most recently, Law No. 27 of 2022 concerning Personal Data Protection (PDP Law). In practice, violations often occur in the form of the distribution and misuse of users' personal data without valid consent. The Personal Data Protection Law (PDP) actually provides more comprehensive protection by affirming the rights of data owners and the obligations and responsibilities of fintech providers to maintain user data confidentiality. However, its implementation remains weak due to a lack of oversight and legal awareness among both providers and users.